Respuesta :
All you have to do to solve this equation is plug the equation you have that already is manipulated for y. Y=2X+3 and substitute it into the equation for y in the first equation, 2x-y=7. So it becomes 2x-(2x+3)=7. By distributing the - sign into the brackets we get 2x-2x-3=7. 0-3=7. -3 does not equal 7. Thus I would think the answer is no solution.
The system of equations has no solution
How to determine the solution?
The system of equations is given as:
2x – y = 7
y = 2x + 3
Substitute y = 2x + 3 in 2x – y = 7
2x – (2x + 3) = 7
Expand
2x - 2x - 3 = 7
Evaluate the like terms
-3 = 7
The above is false.
Hence, the system of equations has no solution
Read more about system of equations at:
https://brainly.com/question/14323743
#SPJ5